MATLAB/simulink study of multi-level inverter topologies using minimized quantity of switches - Krishna, B.Vijaya; Venkata Prashanth, B.; Sujatha, P. (International Journal of Engineering and Technology, 2017)
Multilevel Inverters (MLI) have very good features when compared to Inverters. But using more switches in the conventional configuration will reduce its application in a wider range. For that reason a modified 7-level MLI Topology is presented. This new topology consists of less number of switches that can be reduced to the maximum extent and a separate gate trigger circuit. This will reduce the switching losses, reduce the size of the multilevel inverter, and cost of installation. This new topology can be used in Electrical drives and renewable energy applications. Performance of the new MLI is tested via. Total harmonic distortion. This construction structure of this multilevel inverter topology can also be increased for 9-level, 11-level and so on and simulated by the use of MATLAB/SIMULINK. A separate Carrier Based PWM Technique is used for the pulse generation in this configuration.